Preoperative nTMS and Intraoperative Neurophysiology - A Comparative Analysis in Patients With Motor-Eloquent Glioma - Rosenstock, Tizian; Tuncer, Mehmet Salih; Münch, Max Richard; Vajkoczy, Peter; Picht, Thomas; Faust, Katharina (Frontiers in Oncology, 2021)
Background The resection of a motor-eloquent glioma should be guided by intraoperative neurophysiological monitoring (IOM) but its interpretation is often difficult and may (unnecessarily) lead to subtotal resection. Navigated transcranial magnetic stimulation (nTMS) combined with diffusion-tensor-imaging (DTI) is able to stratify patients with motor-eloquent lesion preoperatively into high- and low-risk cases with respect to a new motor deficit. Objective To analyze to what extent preoperative nTMS motor risk stratification can improve the interpretation of IOM phenomena Methods In this monocentric observational study, nTMS motor mapping with DTI fiber tracking of the corticospinal tract was performed before IOM-guided surgery for motor-eloquent gliomas in a prospectively collected cohort from January 2017 to October 2020. Descriptive analyses were performed considering nTMS data (motor cortex infiltration, resting motor threshold (RMT), motor evoked potential (MEP) amplitude, latency) and IOM data (transcranial MEP monitoring, intensity of monopolar subcortical stimulation (SCS), somatosensory evoked potentials) to examine the association with the postoperative motor outcome (assessed at day of discharge and at 3 months). Results Thirty-seven (56.1%) of 66 patients (27 female) with a median age of 48 years had tumors located in the right hemisphere, with glioblastoma being the most common diagnosis with 39 cases (59.1%). Three patients (4.9%) had a new motor deficit that recovered partially within 3 months and 6 patients had a persistent deterioration (9.8%). The more risk factors of the nTMS risk stratification model (motor cortex infiltration, tumor-tract distance (TTD) ≤8mm, RMTratio <90% / >110%) were detected, the higher was the risk for developing a new postoperative motor deficit, whereas no patient with a TTD >8mm deteriorated. Irreversible MEP amplitude decrease >50% was associated with worse motor outcome in all patients, while a MEP amplitude decrease ≤50% or lower SCS intensities ≤4mA were particularly correlated with a postoperative worsened motor status in nTMS-stratified high-risk cases. No patient had postoperative deterioration of motor function (except one with partial recovery) when intraoperative MEPs remained stable or showed only reversible alterations. Conclusions The preoperative nTMS-based risk assessment can help to interpret ambiguous IOM phenomena (such as irreversible MEP amplitude decrease ≤50%) and adjustment of SCS stimulation intensity.